2015
DOI: 10.1556/aalim.44.2015.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium intake in Hungarian children and adolescents: Comparison of two cross sectional studies

Abstract: The purpose of the study was to assess the sodium and potassium intake among Hungarian children and adolescents. The study was undertaken to estimate daily sodium and potassium intake by measuring 24-h urinary electrolyte excretion rate in 200 Hungarian children (age 1-18 years). Daily sodium and potassium intake positively correlated with age, body mass index, and systolic blood pressure. As a result of the parallel trend and time course of urinary sodium and potassium excretion the sodium to potassium ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Systematic review findings: BMI z-score or BMI Seven studies reported on the association between sodium intake and either BMI or BMI zscore (5,7,9,113,114,117,125) , due to discrepancies in methods used to report data none of these could be pooled (Table S15). Four studies reported on the correlation between sodium intake and BMI/BMI z-score; two reported a moderate significant positive correlation (114,117) , one a very weak significant correlation and one a null relationship (125) . The remaining three studies adjusted for a number of covariates and all reported positive associations between sodium intake and BMI/BMI z-score (5,7,9) .…”
Section: Primary Adiposity Outcome: Bmi Z-score or Bmimentioning
confidence: 99%
See 4 more Smart Citations
“…Systematic review findings: BMI z-score or BMI Seven studies reported on the association between sodium intake and either BMI or BMI zscore (5,7,9,113,114,117,125) , due to discrepancies in methods used to report data none of these could be pooled (Table S15). Four studies reported on the correlation between sodium intake and BMI/BMI z-score; two reported a moderate significant positive correlation (114,117) , one a very weak significant correlation and one a null relationship (125) . The remaining three studies adjusted for a number of covariates and all reported positive associations between sodium intake and BMI/BMI z-score (5,7,9) .…”
Section: Primary Adiposity Outcome: Bmi Z-score or Bmimentioning
confidence: 99%
“…Eighteen cross-sectional studies reported on the relationship between Na intake and a measure of adiposity (5,7,9,12,55,(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125) ; three of which were included in meta-analyses (online Supplementary Table S13). One of these studies was from Canada (124) , one from Iran (123) and the other from South Korea (118) .…”
Section: Children: Cross-sectional Studies (Adiposity Outcomes)mentioning
confidence: 99%
See 3 more Smart Citations